2007
DOI: 10.1038/nrn2254
|View full text |Cite
|
Sign up to set email alerts
|

Patterning and axon guidance of cranial motor neurons

Abstract: The cranial motor nerves control muscles involved in eye, head and neck movements, feeding, speech and facial expression. The generic and specific properties of cranial motor neurons depend on a matrix of rostrocaudal and dorsoventral patterning information. Repertoires of transcription factors, including Hox genes, confer generic and specific properties on motor neurons, and endow subpopulations at various axial levels with the ability to navigate to their targets. Cranial motor axon projections are guided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
193
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(195 citation statements)
references
References 170 publications
2
193
0
Order By: Relevance
“…Thus, at all axial levels, TSHZ3 was coexpressed with PHOX2b in postmitotic bm and vm motoneurons. Coimmunodetection of TSHZ3 with Nkx2.2 (data not shown) confirmed that TSHZ3ϩ cells located ventrally in the mantle layer derived from the vm/bm neuron progenitor (p3) domain (Guthrie, 2007). At E11.5, the ventral bm/vm neurons in the caudal hindbrain had migrated dorsally to form the dorsal motor nucleus of the vagus nerve (dmnX) and the nA.…”
Section: Tshz3 Is Expressed In a Subset Of Developing Cranial Motoneumentioning
confidence: 70%
See 2 more Smart Citations
“…Thus, at all axial levels, TSHZ3 was coexpressed with PHOX2b in postmitotic bm and vm motoneurons. Coimmunodetection of TSHZ3 with Nkx2.2 (data not shown) confirmed that TSHZ3ϩ cells located ventrally in the mantle layer derived from the vm/bm neuron progenitor (p3) domain (Guthrie, 2007). At E11.5, the ventral bm/vm neurons in the caudal hindbrain had migrated dorsally to form the dorsal motor nucleus of the vagus nerve (dmnX) and the nA.…”
Section: Tshz3 Is Expressed In a Subset Of Developing Cranial Motoneumentioning
confidence: 70%
“…Hox and Tshz genes are critical for segment identity, and in Drosophila TSHZ acts as a cofactor of HOX proteins (Manfroid et al, 2004;Taghli-Lamallem et al, 2007). Interestingly, Tshz3 mutation affects motor activity and breathing rhythms, two activities that are also controlled by Hox genes (Chatonnet et al, 2003; Guthrie, 2007). Thus, Tshz3 may be considered to be one of the key regulators of neonatal breathing behavior.…”
Section: Tshz3 Mutation Impairs Survival Of Motoneurons Of the Nucleumentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining these functions is achieved by communicating between central/ peripheral nervous systems via ascending/descending reticular networks. Brainstem centers, including cranial nerve, respiration, auditory, and precerebellar nuclei, process sensory/motor information to mediate these high-order activities (Altman and Bayer, 1997;Wang and Zoghbi, 2001;Ryugo and Parks, 2003;Milsom et al, 2004;Oertel and Young, 2004;Guthrie, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The hindbrain serves as an excellent system to study regional specification and pattern formation, as its early development is devoted to the formation of 7 to 8 repetitive segments, termed rhombomeres, along the anteriorposterior (AP) axis of all vertebrates [3]. Each rhombomere is a lineage-restricted compartment which underlies unique patterns of gene expression, neural crest migration and neuronal differentiation [4][5][6][7][8][9][10][11][12]. Individual rhombomeres are separated from their neighbors by well-defined boundaries.…”
Section: Introductionmentioning
confidence: 99%